Freezing of gait in Chinese patients with multiple system atrophy: prevalence and risk factors - Chen, Yalan; Wang, Hui; Huang, Hongyan; Chen, Yangmei; Xu, Yanming (Frontiers in Neuroscience, 2023)
Objective: Freezing of gait (FOG) is common in neurodegenerative forms of atypical parkinsonism, but few studies have examined FOG in multiple system atrophy (MSA). In this study, we examined the prevalence of freezing of gait and its relationship to clinical features in a large cohort of Chinese MSA patients. Methods: This exploratory study included 202 Chinese patients with probable MSA. FOG was defined as a score ≥ 1 on item 14 of the Unified Parkinson’s Disease Rating Scale. Patients with or without FOG were compared in terms of the Unified MSA Rating Scale (UMSARS) as well as cognitive and neuropsychiatric assessments. Results: The frequency of FOG was 48.0%, 52.1%, and 38.7% in MSA, MSA with predominant parkinsonism (MSA-P), and MSA with predominant cerebellar ataxia (MSA-C), respectively. FOG was associated with worse subscores on parts I, II and IV of the UMSARS as well as worse total UMSARS score; greater likelihood of speech difficulties, falls, gait impairment and balance disorder; more severe symptoms of anxiety and depression; and lower activities of daily living. The binary logistic regression model indicated that higher total UMSARS scores were associated with FOG in MSA, MSA-P, and MSA-C patients. Conclusions: Freezing of gait may be common among Chinese MSA patients, FOG may correlate with severe motor symptoms, anxiety, depression and activities of daily living. Total UMSARS score may be an independent risk factor for FOG.